Epidemiological profile and risk factors associated with death in patients receiving invasive mechanical ventilation in an adult intensive care unit from Brazil: a retrospective study - Palamim, Camila Vantini Capasso; Boschiero, Matheus Negri; Marson, Fernando Augusto Lima (Frontiers in Medicine, 2023)
Introduction Understanding the epidemiological profile and risk factors associated with invasive mechanical ventilation (IMV) is essential to manage the patients better and to improve health services. Therefore, our objective was to describe the epidemiological profile of adult patients in intensive care that required IMV in-hospital treatment. Also, to evaluate the risks associated with death and the influence of positive end-expiratory pressure (PEEP) and arterial oxygen pressure (PaO2) at admission in the clinical outcome. Methods We conducted an epidemiological study analyzing medical records of inpatients who received IMV from January 2016 to December 2019 prior to the Coronavirus Disease (COVID)-19 pandemic in Brazil. We considered the following characteristics in the statistical analysis: demographic data, diagnostic hypothesis, hospitalization data, and PEEP and PaO2 during IMV. We associated the patients’ features with the risk of death using a multivariate binary logistic regression analysis. We adopted an alpha error of 0.05. Results We analyzed 1,443 medical records; out of those, 570 (39.5%) recorded the patients’ deaths. The binary logistic regression was significant in predicting the patients’ risk of death [X2(9) = 288.335; p < 0.001]. Among predictors, the most significant in relation to death risk were: age [elderly ≥65 years old; OR = 2.226 (95%CI = 1.728–2.867)]; male sex (OR = 0.754; 95%CI = 0.593–0.959); sepsis diagnosis (OR = 1.961; 95%CI = 1.481–2.595); need for elective surgery (OR = 0.469; 95%CI = 0.362–0.608); the presence of cerebrovascular accident (OR = 2.304; 95%CI = 1.502–3.534); time of hospital care (OR = 0.946; 95%CI = 0.935–0.956); hypoxemia at admission (OR = 1.635; 95%CI = 1.024–2.611), and PEEP >8 cmH2O at admission (OR = 2.153; 95%CI = 1.426–3.250). Conclusion The death rate of the studied intensive care unit was equivalent to that of other similar units. Regarding risk predictors, several demographic and clinical characteristics were associated with enhanced mortality in intensive care unit patients under mechanical ventilation, such as diabetes mellitus, systemic arterial hypertension, and older age. The PEEP >8 cmH2O at admission was also associated with increased mortality since this value is a marker of initially severe hypoxia.